2021
DOI: 10.7150/ijms.62530
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of melanogenesis by Aster yomena callus pellet extract in melanoma cells and patients with skin pigmentation

Abstract: Plant tissue culture holds immense potential for the production of secondary metabolites with various physiological functions. We recently established a plant tissue culture system capable of producing secondary metabolites from Aster yomena . This study aimed to uncover the mechanisms underlying the potential therapeutic effects of Aster yomena callus pellet extract (AYC-P-E) on photoaging-induced skin pigmentation. Excessive melanogenesis was induced in B16F10 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…ERK may be suppressed by Ardisia crenata leaf and small branch extract [ 130 ] and by lupenone, a triterpenoid, isolated from Erica multiflora leaf [ 131 ]. In contrast, ERK may be upregulated, and melanogenesis suppressed, by Astragalus membranaceus whole plant extract [ 132 ], Aster yomena callus pellet extract [ 133 ], Melochia corchorifolia whole plant extract [ 134 ], Artemisia capillaris whole plant extract [ 135 ], Orostachys japonicus whole plant extract [ 136 ], and Aster spathulifolius leaf extract treatment [ 137 ]. Similar effects are also triggered by 2-[4-(3-hydroxypropyl)-2-methoxyphenoxy]-1,3-propanediol isolated from Juglans mandshurica fruits [ 138 ], 1-O-acetylbritannilactone from Inula britannica flowers [ 139 ], zerumbone, a sesquiterpenoid, from Zingiber officinale [ 140 ], octaphlorethol A, a phenolic compound, from Ishige foliacea [ 141 ], 2-[4-(3-hydroxypropyl)-2-methoxyphenoxy]-1,3-propanediol from Juglans mandshurica fruits [ 138 ], loganin, an iridoid monoterpenoid, from Cornus officinalis [ 111 ], neobavaisoflavone, a 7-hydroxyisoflavone, from aerial parts of Pueraria lobata [ 142 ], 6-O-isobutyrylbritannilactone from Inula britannica flowers [ 128 ] and quercitrin, a quercetin O-glycoside, from Lindera obtusiloba leaves [ 143 ].…”
Section: Mechanisms Of Melanogenesis-related Signaling Pathway Modula...mentioning
confidence: 99%
See 2 more Smart Citations
“…ERK may be suppressed by Ardisia crenata leaf and small branch extract [ 130 ] and by lupenone, a triterpenoid, isolated from Erica multiflora leaf [ 131 ]. In contrast, ERK may be upregulated, and melanogenesis suppressed, by Astragalus membranaceus whole plant extract [ 132 ], Aster yomena callus pellet extract [ 133 ], Melochia corchorifolia whole plant extract [ 134 ], Artemisia capillaris whole plant extract [ 135 ], Orostachys japonicus whole plant extract [ 136 ], and Aster spathulifolius leaf extract treatment [ 137 ]. Similar effects are also triggered by 2-[4-(3-hydroxypropyl)-2-methoxyphenoxy]-1,3-propanediol isolated from Juglans mandshurica fruits [ 138 ], 1-O-acetylbritannilactone from Inula britannica flowers [ 139 ], zerumbone, a sesquiterpenoid, from Zingiber officinale [ 140 ], octaphlorethol A, a phenolic compound, from Ishige foliacea [ 141 ], 2-[4-(3-hydroxypropyl)-2-methoxyphenoxy]-1,3-propanediol from Juglans mandshurica fruits [ 138 ], loganin, an iridoid monoterpenoid, from Cornus officinalis [ 111 ], neobavaisoflavone, a 7-hydroxyisoflavone, from aerial parts of Pueraria lobata [ 142 ], 6-O-isobutyrylbritannilactone from Inula britannica flowers [ 128 ] and quercitrin, a quercetin O-glycoside, from Lindera obtusiloba leaves [ 143 ].…”
Section: Mechanisms Of Melanogenesis-related Signaling Pathway Modula...mentioning
confidence: 99%
“…In B16 melanoma cells, Musa sapientum peel extract [ 160 ], Aster yomena callus pellet extract [ 133 ] and Orostachys japonicus whole plant [ 136 ] treatment reduced phosphorylation of AKT, and these might act as anti-melanogenesis agents. Upregulation of AKT by Phragmites communis leaf extract [ 149 ], Aster spathulifolius leaf extract treatment [ 137 ] and Ginkgo biloba leaf extract [ 161 ] may also inhibit melanin synthesis.…”
Section: Mechanisms Of Melanogenesis-related Signaling Pathway Modula...mentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9] Thus, modulating the activity of enzyme cascades consisting of several key enzymes, such as TRY, TRP-1, and TRP-2, is considered an important strategy in the development of skin pigmentation treatments. 10,11 Microphthalmia-associated transcription factor (MITF) is involved in the survival, proliferation, and differentiation of melanocytes and is an important transcriptional regulator of TRY, TRP-1, and TRP-2. 12,13 The key players in UV-mediated MITF regulation are propiomelanocortin (POMC), α-melanocyte-stimulating hormone (α-MSH), stem cell factor (SCF), and endothelin-1 (ET-1), all of which induce melanogenesis through four major signaling pathways: the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT) signaling pathway, and (4) Wnt/β-catenin signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we established a callus culture system for Aster yomena ( A. yomena ) and demonstrated the various bioactivities of substances derived from A. yomena callus, such as anti-photoaging, anti-melanogenic, and anti-inflammatory effects [ 22 , 23 ]. We found that the A. yomena callus culture system could induce EV formation, resembling the induction of EV formation in other plant species, and that these EVs contained secondary metabolites with various immunological effects.…”
Section: Introductionmentioning
confidence: 99%